Human Capital Development as a Predictor Firm Growth in Manufacturing Companies in Lagos State (International Journal of Scientific Research and Management (IJSRM), 2022)
The main purpose of this study was to investigate the effect of human capital development on firm growth in Manufacturing companies, Lagos State. The study employed descriptive survey design and the target population of the study was 2,355 employees from the three selected manufacturing companies listed in the Nigeria Stock Exchange. The simple random sampling method was used in selecting the respondents in each of the selected manufacturing company. The sample size was 418. The study used questionnaire to collect the required data. Descriptive statistics was used mainly to summarize the data. Statistical Package for Social Science (SPSS) was used for analysing data. Data presentation was through the use of tables. Regression analysis was used to establish the relationship between the independent and dependent variables. The study found out that employee work experience had no significant effect on organizational output of selected manufacturing companies in Lagos State, Nigeria (β = 0.045, t = 1.122, p > 0.05. Employee training had a significant effect on market share of selected manufacturing companies in Lagos State, Nigeria (β = 0.101, t = 2.354, p < 0.05). In addition, employee compensation had a significant effect on organisational profit of selected manufacturing companies in Lagos State, Nigeria (β = 0.225, t = 4.515, p < 0.05). The study recommends that managers of selected manufacturing companies should improve the staff competence according to the company’s expectation; providing training to the employee by emphasizing on the hard skills and soft skills, as well as expertise skill; understand the amount of compensation in accordance with the environment of the manufacturing industry in Nigeria in order to encourage the employees in improving their performance.